Application of the Finite Element Method (FEM) to Analyze the Mechanical Behavior of Piezoelectric Materials When an Electric Field Is Applied to a Piezoelectric Structure (Inverse Piezoelectricity) - Mehdi Boudouh; Brahim El Khalil Hachi; Mohamed Haboussi; Sadam Houcine Habib (Engineering Proceedings)
Modeling the inverse impact of piezoelectricity on the mechanical response of smart (piezoelectric) materials through the finite element method (FEM) requires a comprehensive framework that encompasses a multitude of components and intricacies. The utilization of the FEM by researchers is aimed at scrutinizing and comprehending the complex interplay between the mechanical response and piezoelectric characteristics of smart materials. The process of modeling entails the application of numerical methods that facilitate the examination of the reverse effects of piezoelectricity on mechanical behavior with a high degree of precision and accuracy. Through the FEM, a robust and efficient approach is provided to replicate the intricate behavior and response of smart materials under diverse loading conditions, taking into account the intricate interactions between the mechanical and electrical domains. By adopting this modeling strategy, researchers can acquire valuable insights into the fundamental mechanisms and phenomena that govern the inverse influence of piezoelectricity, thereby laying the groundwork for the advancement of cutting-edge smart materials with enhanced performance and functionality. Consequently, the modeling of the inverse effects of piezoelectricity on the mechanical behavior of smart materials using the finite element method emerges as a pivotal and indispensable facet of material science research, playing a significant role in propelling progress across various domains such as robotics, energy harvesting, and structural health monitoring. The primary aim of this research paper is to simulate the impact of inverse piezoelectricity on the mechanical behavior of piezoelectric materials; we have employed the principles of continuum mechanics to address both mechanical and electrical aspects in order to compute the mechanical field when an electric field is administered to the piezoelectric configuration.